2017
DOI: 10.1016/j.preteyeres.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Primary angle closure glaucoma: What we know and what we don’t know

Abstract: Primary angle-closure glaucoma (PACG) is a common cause of blindness. Angle closure is a fundamental pathologic process in PAGC. With the development of imaging devices for the anterior segment of the eye, a better understanding of the pathogenesis of angle closure has been reached. Aside from pupillary block and plateau iris, multiple-mechanisms are more common contributors for closure of the angle such as choroidal thickness and uveal expansion, which may be responsible for the presenting features of PACG. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
222
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(265 citation statements)
references
References 152 publications
6
222
0
12
Order By: Relevance
“…The cost‐effectiveness of such a prophylactic intervention is currently unknown (Sun et al. ). Plateau iris syndrome (which occurs in one‐third of eyes with PACS) and a prominent lens vault are other mechanisms of angle closure which are not addressed by LPI, and could result in residual angle closure and eventual glaucomatous damage after LPI (He et al.…”
Section: Discussionmentioning
confidence: 99%
“…The cost‐effectiveness of such a prophylactic intervention is currently unknown (Sun et al. ). Plateau iris syndrome (which occurs in one‐third of eyes with PACS) and a prominent lens vault are other mechanisms of angle closure which are not addressed by LPI, and could result in residual angle closure and eventual glaucomatous damage after LPI (He et al.…”
Section: Discussionmentioning
confidence: 99%
“…The eyes with the presence of iridotrabecular contact and an elevated IOP or PAS with no secondary cause for the PAS, but without glaucomatous optic neuropathy were defined as PAC. 8 We excluded eyes that had received pilocarpine treatment within a week at the time of the study; that had extensive PAS (more than three clock-hours) that could affect the iris and angle configuration; that had previous laser or intraocular surgery; and that had secondary angle closure, such as exfoliation syndrome, iris neovascularization, lens intumescence, or subluxation and uveitis.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…However, myopia by the definition of the refractive status in angle-closure patients is often misleading. It is well known that PAC usually occurs in the population older than 40 years, 8 so the myopia formation in these patients might be due to an agerelated increase in the refractive index of the lens. A population-based study revealed that myopia is related to nuclear cataract rather than axial length (AL) among people aged 40 to 80 years.…”
mentioning
confidence: 99%
“…There was no significant difference in age, gender or ethnicity between the case and control groups. The inclusion criteria are based on the diagnostic criteria for PACG issued by the International Society of Geographical and Epidemiological Ophthalmology (ISGEO) [18]: (i) primary angle closure suspect (PACS): an eye in which appositional contact between the peripheral iris and posterior trabecular meshwork is considered possible, (ii) primary angle closure (PAC): an eye with an occludable angle and features indicating that trabecular obstruction by the peripheral iris has occurred. The optic disc does not have glaucomatous damage, (iii) PACG: PAC together with evidence of glaucomatous optic neuropathy.…”
Section: Methodsmentioning
confidence: 99%